Sytuacja edukacyjna dwujęzycznych uczniów z trudnościami w uczeniu się w szkole Hand in Hand w Jerozolimie - Perelmuter, Idit (Studia Edukacyjne, 2018)
This article will address the educational situations with which bilingual students who have learning disabilities cope in the education system and in the bilingual schools of Hand in Hand, an association which was established to promote and develop a shared society for Arabs and Jews in Israel. In addition, it will describe the difficulties of the learning-disabled bilingual students and how they impact upon the student. The first part will present the educational concept of Hand in Hand and the reality of the bilingual school in Jerusalem in particular. The second part will describe educational situations in which bilingual students who have learning disabilities cope in the bilingual school of the Hand in Hand Association. Furthermore, it will address the difficulties of these students in the school. The third part focuses upon the relationship between the ecological model of Bronfenbrenner and neuro-developmental theory and the educational situations of learning-disabled bilingual students, with an emphasis on their immediate environment (the educational situations described in the article are taken from professional experience in my work in the bilingual school in Jerusalem as an inclusion teacher for learning-disabled bilingual students both in the elementary and middle schools).